Control Financiero De Los Productos No Asegurados “Magap Los Ríos - Benavides Domínguez, Elizabeth Gardenia (2018)
The agricultural sector is a primordial source for the Ecuadorian economy, serving as advantage for the socio-economic development of Ecuador. Currently the public sector encourages medium and small farmers with projects to ensure their products. Granting subsidies for crop losses, which are affected by environmental or biological accidents. Being part of the Agro-Seguro project the provinces of Los Ríos, Guayas, Manabí, Bolívar, etc. Insurance project created by the Ministry of Agriculture through MAGAP, in which there are products that are not under the stipulations established in the Agro-Insurance regulations; itself, causing a lack of control for production and marketing of products such as pigeon pea and passion fruit. Affecting the farmers in financial investment losses without the ability to be recovered; in the sale of products at low prices either directly or through intermediaries and decrease of liquidity for the next sowing cycles. During the 2016 and 2017 periods, farmers who grow beans, passion fruit and passion fruit they have experienced a decrease in income and an increase in their costs; getting minimum returns, which is why we opted for the development of the present study case called: financial control of MAGAP's uninsured products. Rivers